Part 2. (1st June 2015) - Stengers, Isabelle; Smith, Tracy K.; Davis, Christine
Entries: An Eternal Object, Value, Infection, A Confidence of Two, Endurance, Awareness, Experience. Includes text by Isabelle Stengers from Thinking with Whitehead, Christine Davis and Scott Lyall. Artworks by Wael Shawky, Paul P., Christine Davis, Adrian Piper, Terry Adkins, Chris Curreri. Poem by Tracy K. Smith